Are the pharmacokinetic parameters of low molecular weight heparins predictive of their clinical efficacy? - Andrassy, Konrad; Eschenfelder, Volker (Thrombosis research, 1996)
Low molecular weight heparins (LMWHs) are obtained by partial enzymatic or chemical depolymerisation and further chromatographic separation of standard unfractionated heparin. Most pharmacokinetic studies of LMWHs in humans have utilised the anticoagulant action against activated clotting factors. LMWH contains both high and low affinity fragments to antithrombin-III. Antithrombotic efficacy of LMWH is dependent on both fragments. LMWH levels peak 10 minutes after intravenous administration and are detectable for 5-8 hours. Following subcutaneous administration, maximum anti-factor Xa levels are demonstrable up to 12 hours or longer. Anti-factor IIa activity is eliminated faster than anti-factor Xa activity when measured with chromogenic substrates, but not with thrombin generation. The half-lives of the various LMWHs and their bioavailability, as measured by their anti-factor Xa or anti-factor IIa activities differ to a certain extent and clinical efficacy cannot be predicted from such data. On the basis of clinical studies, the antithrombotic potential of s.c. LMWHs for general surgery lies approximately around 2000 anti-factor Xa units and for high-risk patients around 4000 anti-factor Xa units, with no increased bleeding tendency. This is derived from investigations with enoxaparin, reviparin and dalteparin and is not valid for other LMWH derivatives.